Returns to Acquirers in Indian Aviation Mergers: A Study - Mohapatra, Jayanta Kumar; Yadav, Manish (Indian Journal of Finance, 2014)
Mergers, acquisitions, and other forms of business combinations have become more phenomenal nowadays and have significantly increased in both number and volume. Though the Indian aviation industry has fewer numbers of players, but it has also witnessed major M&As in the past, and many joint ventures are in the process. The present paper exposed the financial performance of the mergers, particularly the gain or loss to the shareholders of the acquiring companies. Event study methodology (to judge the abnormal gains as a result of the mergers) and accounting methodology (to judge operating performance) were used in the present study . The study revealed that mergers were predicted and benefited the shareholders, thereby giving a push to the share prices of the acquiring company in general, but the operating performance in the long run was not impressive.